A transdiagnostic approach to investigate of the relationships between anxiety sensitivity and health anxiety: the mediated roles of distress tolerance and emotion regulation - Hamid Mohsenabadi; Mohammadreza Pirmoradi; Komeil Zahedi Tajrishi; Banafsheh Gharraee (Frontiers in Psychiatry)
BackgroundEmotion regulation (ER) and distress tolerance (DT) are considered transdiagnostic risk factors for a range of anxiety disorders. This study investigated the relationship between anxiety sensitivity (AS) and health anxiety (HA) in the general population, focusing on the mediating roles of DT and ER.MethodsThe study was conducted as a cross-sectional survey from October to December 2023 in Tehran Province, Iran. A total of 971 individuals participated in this study (52.8% female; mean age 39.04 years, SD=10.64). Participants completed self-report questionnaires to assess HA (The Short Health Anxiety Inventory), AS (The Anxiety Sensitivity Index-3), DT (The 15-item Distress Tolerance Scale) and ER (The 10-item Emotion Regulation Questionnaire). We used structural equation modeling (SEM) to examine the hypothesis that DT and ER would mediate the relationship between AS and the HA.ResultsAS was modestly related to all measures (r from -0.40 to 0.55). According to the SEM analysis, AS (β = 0.45, 95%CI [0.34, 0.56]) had a significant direct effect on HA. However, the analysis of the indirect effects revealed that both DT (β = 0.10, 95% CI [0.06, 0.16]) and emotion regulation strategies—cognitive reappraisal (β = 0.06, 95% CI [0.01, 0.11]) and expressive suppression (β = 0.11, 95% CI [0.06, 0.18])—act as partial mediators in the relationship between AS and HA.ConclusionsAS plays a crucial role in predisposing individuals to HA. The mediating roles of DT and ER provide insight into the link between AS and HA. Nevertheless, the study’s cross-sectional design and reliance on a non-clinical sample limit the applicability of the results. Further research involving different samples and intervention studies is needed to validate and expand upon these findings.